Effect of two levels of “laritaco” flour (Vernonanthura patens) on the productive performance and intestinal morphometry in broilers - Apolo Arévalo, Guido Manuel (2021)
The aim of this study was to evaluate the effect of two levels (0.5 and 1%) of inclusion of “laritaco” flour (Vernonanthura patens) on the productive behavior and intestinal morphometry of broilers. In total, 588 male chicks of the Cobb 500 line were used, distributed in a block design in three treatments with seven repetitions each, considering a group of 28 chickens as an experimental unit. There were no differences between treatments in feed consumption, body weight and feed conversion; however, an increase in the length of the intestine segments was observed, as well as wider intestinal villi and shallower crypts.